Efektivitas Media Ular Tangga Dalam Pendidikan Kesehatan Gigi Dan Mulut Siswa SDN 1 Gereba Kabupaten Ciamis - Iis Ismayanti; Winda Siti Nurkholipah; Resa Rahmasuli; Deana Sulistiani; Wahyu `` Dwisuhardjono; Zeni Nurfalah (Yayasan Inspirasi El Burhani, 2021)
Introduction : Dental and oral health education is an effort to influence someone to behave well and motivate them to maintain dental and oral health, as well as increase public awareness of the importance of dental and oral health and provide an understanding of ways to maintain dental and oral health. Objective : The purpose of this community service is to increase children's knowledge and understanding of dental and oral health, and to improve good and correct brushing habits for elementary school students. Method : the method used is the lecture and demonstration method, namely by playing while learning to use the help of the snake ladder educational game banner. Then take respondents from class 4 SDN 1 Gereba as many as 20 people and samples taken only 3 people, 30 minutes of playing time interspersed with questions and answers according to the questions already available in each column of snakes and ladders. The activities included the introduction of basic material on dental and oral health, then Health Education was carried out by 6 extension workers by playing and learning with the help of snakes and ladders educational media as well as material presentation which then did a role play on how to brush teeth properly and correctly. Result : Health education about teeth and mouth using lecture and demonstration methods with the help of the snake and ladder educational game banner media which was carried out on school-age children with 20 respondents and a sample of 3 people, the use of this media was effective in increasing children's dental and oral health knowledge.